KORELASI NILAI TIME REPETITION (TR) DAN TIME ECHO (TE) TERHADAP SIGNAL TO NOISE RATIO (SNR) PADA CITRA MRI - Aji Prastowo, Alan Tanjung; Setiabudi, Wahyu; Anam, Choirul (BERKALA FISIKA, 2013)
Effort to obtain a correlation of TR and TE to the value of Signal to Noise Ratio (SNR) in MRIÂ machine has been carried out. In this research used MRI Hitachi Airis II which has a permanentmagnetic field of 0.3 Tesla. Research using a phantom object with Polyethylene Vessel containingNiCl2: 18 mmol/l. Phantom has a tube diameter 165 mm, cap diameter 120 cm and height 320 mm.Image acquisition is done with two TE value of 20 ms and 120 ms, and TR values varied from 100 msto 4000 ms, with the scale of 100 ms. Slice taken with a thickness 5 mm, and in the position 15 cm fromthe bottom of phantom. Region of interest (ROI) in the image is determined at the radius of 65 cm.SNR calculation is then performed for a variety of TE and TR. It was obtained that the SNR valueincreases exponentially for TR value of 100 ms to 700 ms and stabilized at the next TR to 4000 ms. Atthe same TR, SNR value at TE 20 ms greater than the TE 120 ms. At TE 20 ms, TR optimal value forT1WI is at 700 ms, with a SNR value of 57,6 ms, whereas for PD image on TR 3900 ms with a SNR of57,6. At TE 120 ms, TR optimal value for T2WI was at 2200 ms with SNR value of 19.Keywords: Magnetic Resonance Imaging (MRI), Time Repetition (TR), Time Echo (TE), Signal toNoise Ratio (SNR)